2022
DOI: 10.1093/jxb/erac119
|View full text |Cite
|
Sign up to set email alerts
|

Impaired auxin signaling increases vein and stomatal density but reduces hydraulic efficiency and ultimately net photosynthesis

Abstract: Auxins are known to regulate xylem development in plants, however, their effects on water transport efficiency are poorly known. Here we used tomato plants of the diageotropica mutant (dgt), which has impaired function of a Cyclophilin 1 cis/trans isomerase involved in auxin signaling, and its corresponding wild type (WT) to explore its effects on plant hydraulics and leaf gas exchange. The xylem conduits of dgt showed a reduced hydraulically-weighted vessel diameter (Dh) (24-43%) and conduit number (25-58%) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 51 publications
4
8
0
Order By: Relevance
“…The vulnerability curves showed 50 values significantly more negative for the dgt mutant, consistent with the reported trend of higher embolism resistance in species with reduced vessel diameter and higher (t/b) 3 . In this study, we confirmed the reductions in conduit diameter in leaves of the dgt mutant as previously observed Andrade et al, 2022). This result suggests an association of DGT function with the regulation of cell expansion during the development of leaf xylem conduits.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The vulnerability curves showed 50 values significantly more negative for the dgt mutant, consistent with the reported trend of higher embolism resistance in species with reduced vessel diameter and higher (t/b) 3 . In this study, we confirmed the reductions in conduit diameter in leaves of the dgt mutant as previously observed Andrade et al, 2022). This result suggests an association of DGT function with the regulation of cell expansion during the development of leaf xylem conduits.…”
Section: Discussionsupporting
confidence: 92%
“…The tomato mutant dgt has been recently described as presenting smaller Dh compared to its wild-type (Batista- Andrade et al, 2022), which provides an opportunity to assess whether changes in the xylem structure affect embolism resistance within this species. Associated with the reduction in Dh, dgt showed lower stomatal conductance and higher intrinsic water use efficiency (Andrade et al, 2022). We hypothesize that the conduit diameter reduction in dgt will result in greater resistance to drought-induced embolism, which might provide greater water deficit tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Samples from the middle portion of leaf blades (avoiding the midrib) were obtained, and then stored and processed for posterior analyses exactly as described elsewhere [ 67 ]. For each sample, five fields of view were used for measuring SD, SI, and SS.…”
Section: Methodsmentioning
confidence: 99%
“…An efficient coordination of plant hydraulics and photosynthesis is therefore essential for the synchronized regulation of water loss and carbon dioxide uptake in plants through the stomata. This coordination has recently been evidenced in tomato mutants (Andrade et al ., 2022), where a reduction in diameter and number of xylem vessels resulting in lower hydraulic conductivity was associated with a 50% and 25% reduction in stomatal conductance and net photosynthesis, respectively.…”
Section: Hydraulic Properties and Crop Productivity Under Drought Con...mentioning
confidence: 99%